The discrepancy between patient expectations and realistic outcomes in aesthetic plastic surgery: A comparative analysis - Raitez, Skarlett Ribeiro; Rocha, Fernanda Rodrigues; Jung, Luana; Oliveira, Larissa de Sousa; Venancio, Wesley Felipe; Mittelmann , Iara Carolini; Gallas, Fernanda; Fontes, Amanda Muniz; Fernandes, Marcyelle Severo; Gonçalves , Kelli da Silva (Seven Editora, 2023)
Cosmetic plastic surgery has become increasingly popular in recent years, with individuals seeking various procedures to improve their physical appearance. However, an important issue that arises in this field is the discrepancy between patient expectations and the realistic outcomes of these surgeries. In addition, strategies to improve communication between patients and surgeons and manage patient expectations will be discussed. To begin with, it is essential to understand the fundamentals of cosmetic plastic surgery. This overview will cover the definition of cosmetic plastic surgery, the different types of procedures available, and the common motivations for individuals to undergo such surgeries. DOI:https://doi.org/10.56238/globalhealthprespesc-040